CD146+ mural cells from infantile hemangioma display proangiogenic ability and adipogenesis potential in vitro and in xenograft models - Chen, Jialin; Chen, Qianyi; Qiu, Yajing; Chang, Lei; Yu, Zhang; Li, Yuanbo; Chang, Shih-jen; Chen, Zongan; Lin, Xiaoxi (Frontiers in Oncology, 2023)
Objective: Infantile hemangioma (IH), the most common infantile vascular neoplasm, is uniquely characterized by rapid proliferation followed by slow spontaneous involution lasting for years. In IH lesions, perivascular cells are the most dynamic cell subset during the transition from the proliferation phase to the involution phase and we aimed to study this kind of cells systematically. Methods and Results: CD146-selective microbeads were used to isolate IH-derived mural-like cells (HemMCs). Mesenchymal markers of HemMCs were detected by flow cytometry and multilineage differentiation potential of HemMCs were detected by specific staining after conditioned culture. CD146-selected nonendothelial cells from IH samples showed characteristics of mesenchymal stem cells with distinct angiogenesis-promoting effects detected by transcriptome sequencing. HemMCs spontaneously differentiated into adipocytes 2 weeks after implantation into immunodeficient mice, and almost all HemMCs had differentiated into adipocytes within 4 weeks. HemMCs could not be induced to differentiate into endothelial cells in vitro. However, 2 weeks after implantation in vivo, HemMCs in combination with HUVECs formed GLUT1+ IH-like blood vessels, which spontaneously involuted into adipose tissue 4 weeks after implantation. Conclusions: In conclusion, we identified a specific cell subset that not only showed behavior consistent with the evolution of IH but also recapitulated the unique course of IH. Thus, we speculate that proangiogenic HemMCs may be a potential target for the construction of hemangioma animal models and the study of IH pathogenesis.